End-effector wheeled robotic arm gaming prototype for upper limb coordination control in home-based therapy - Ahmad Hoirul Basori (Universitas Ahmad Dahlan, 2020)
The stroke patient will be having difficulty to control their upper limb, which causes their handling to become weak and unorganized. Conventional therapy designed to retrain the subject ability when it's losses due to stroke. As previous study concern that a subject with strong motivation and concentration of treatment tends to recover better than people who don't follow the program. This research focused on intensifying the training by providing user with Wheel robotic arm to train their upper limb. User will be asked to do exercising on moving particular objects to another position repetitively during a specific period. The robot will help the user to assist and relearn their motoric skill and improve muscle strength and coordination. The result of training is quite convincing when the user gives a positive response toward the practice. Around 86 percent of subject likely prefer the proposed system as their home-based rehabilitation system. The Anova testing with alpha 0.05 shows that there is no significant difference between trained subject and untrained subject on operating the wheeled robotic arm. It's mean the proposed system is reliable and user friendly to be used without an assistant so user can have more flexibility and improve their accomplishment on regaining their motoric skills. The future work will focus on stroke patient testing with more challenge and obstacle in enhancing the effectiveness of the stroke rehabilitation system.